Altered cortical excitability in persistent idiopathic facial pain. (February 2019) - Galhardoni, Ricardo; Ciampi de Andrade, Daniel; Puerta, Mariana YT; Brunoni, Andre R; Varotto, Bruna LR; de Siqueira, José TT; Teixeira, Manoel J; Siqueira, Silvia RDT
Introduction: Persistent idiopathic facial pain is a refractory and disabling condition of unknown mechanism and etiology. It has been suggested that persistent idiopathic facial pain patients have not only peripheral generators of pain, but also central nervous system changes that would contribute to the persistence of symptoms. We hypothesized that persistent idiopathic facial pain would have changes in brain cortical excitability as measured by transcranial magnetic stimulation compared to healthy controls. Methods: Twenty-nine persistent idiopathic facial pain patients were compared to age- and sex-matched healthy controls and underwent cortical excitability measurements by transcranial magnetic stimulation applied to the cortical representation of the masseter muscle of both hemispheres. Single-pulse stimulation was used to measure the resting motor threshold and suprathreshold motor-evoked potentials. Paired-pulse stimulation was used to assess short intracortical inhibition and intracortical facilitation. Clinical pain and associated symptoms were assessed with validated tools. Results: Spontaneous pain was found in 27 (93.1%) and provoked pain was found in two (6.9%) persistent idiopathic facial pain patients. The motor-evoked potentials at 120% and 140% were significantly lower for both hemispheres compared to controls. Persistent idiopathic facial pain patients had lower short-interval intracortical inhibition compared with controls. These changes were correlated with some aspects of quality of life, and higher mood symptoms. These neurophysiological alterations were not influenced by analgesic medication, as similar changes were observed in patients with or without central-acting drugs. Conclusions: Persistent idiopathic facial pain is associated with changes in intracortical modulation involving GABAergic mechanisms, which may be related to certain aspects of the pathophysiology of this chronic pain condition. Trial registration: NTC01746355.